IMPLEMENTATION OF HUMAN RESOURCE MANAGEMENT STRATEGY AT THE INVESTMENT AND ONE-STOP INTEGRATED SERVICE OFFICE FOR THE OPTIMIZATION OF REGIONAL ORIGINAL REVENUE - Roynaldo Richard Hendra Uneputty; Mervin Irian Sadipun Komber; Wa Ode Likewati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study seeks to examine human resource management (HRM) strategies for enhancing local own-source revenue (PAD) at the Investment and One-Stop Integrated Service Office (DPMPTSP) in Sorong Regency, West Papua Province. Using a descriptive qualitative method, data were gathered through in-depth interviews, direct observation, and documentation involving civil servants (ASN) within the DPMPTSP context. The results show that effective coaching, training, and optimal compensation from leadership are key factors in improving the competence, motivation, and performance of civil servants, which positively impacts PAD growth. However, constraints remain, such as lack of transparency in task allocation, suboptimal compensation, and leadership styles that are less participative and innovative. The main recommendations are to increase the frequency of training and benchmarking, refine the reward and compensation system, and strengthen leadership capacity to encourage concrete contributions from civil servants to PAD enhancement. The study also emphasizes the significance of innovation in human resource management and the application of information technology to enhance organizational effectiveness. The study's limitations encompass data subjectivity and a restricted respondent pool. The findings are expected to provide both theoretical and practical contributions for developing HRM strategies in the public sector, especially in the context of improving local government revenue.